Aneuploidy underlies brefeldin A-induced antifungal drug resistance in Cryptococcus neoformans - Zhang, Zhi-hui; Sun, Liu-liu; Fu, Bu-qing; Deng, Jie; Jia, Cheng-lin; Miao, Ming-xing; Yang, Feng; Cao, Yong-bing; Yan, Tian-hua (Frontiers in Cellular and Infection Microbiology, 2024)
Cryptococcus neoformans is at the top of the list of “most wanted” human pathogens. Only three classes of antifungal drugs are available for the treatment of cryptococcosis. Studies on antifungal resistance mechanisms are limited to the investigation of how a particular antifungal drug induces resistance to a particular drug, and the impact of stresses other than antifungals on the development of antifungal resistance and even cross-resistance is largely unexplored. The endoplasmic reticulum (ER) is a ubiquitous subcellular organelle of eukaryotic cells. Brefeldin A (BFA) is a widely used chemical inducer of ER stress. Here, we found that both weak and strong selection by BFA caused aneuploidy formation in C. neoformans, mainly disomy of chromosome 1, chromosome 3, and chromosome 7. Disomy of chromosome 1 conferred cross-resistance to two classes of antifungal drugs: fluconazole and 5-flucytosine, as well as hypersensitivity to amphotericin B. However, drug resistance was unstable, due to the intrinsic instability of aneuploidy. We found overexpression of AFR1 on Chr1 and GEA2 on Chr3 phenocopied BFA resistance conferred by chromosome disomy. Overexpression of AFR1 also caused resistance to fluconazole and hypersensitivity to amphotericin B. Furthermore, a strain with a deletion of AFR1 failed to form chromosome 1 disomy upon BFA treatment. Transcriptome analysis indicated that chromosome 1 disomy simultaneously upregulated AFR1, ERG11, and other efflux and ERG genes. Thus, we posit that BFA has the potential to drive the rapid development of drug resistance and even cross-resistance in C. neoformans, with genome plasticity as the accomplice.